Handheld solar light use, durability, and retention among women and girls in internally displaced persons camps in Haiti — 2013–2014. (September 2016) - Dynes, Michelle; Rosenthal, Mariana; Hulland, Erin; Hardy, Colleen; Torre, Lisandro; Tomczyk, Barbara
Abstract: During conflict and disasters, women and girls are at increased risk of gender based violence. International humanitarian guidelines call for the distribution of individual lighting to meet women and girls' basic needs and to reduce risk of violence; however, little evidence exists to support these guidelines. This paper presents an evaluation of handheld solar light use, retention, and durability among women and girls living in two internally displaced persons camps in Port-au-Prince, Haiti. Data was gathered prospectively via five household surveys from August 2013 to April 2014; a total of 754 females participated in the study. Women reported going outside at night more frequently at the end of the study than at the beginning. The handheld solar lights were the most common source of lighting at endline, whereas candle and gas lamp use declined significantly over time. Results from a Life-Table survival analysis estimated that households had an 83% probability of still owning a functioning light after seven months. Given the frequent use, acceptable durability, and retention of the lights, donors and humanitarian organizations should consider supporting light distribution to women and girls in internally displaced persons camps to help meet their basic needs.